Colocated Mental Health/Developmental Care. (October 2017) - Levy, Sheryl L.; Hill, Elena; Mattern, Kathryn; McKay, Kevin; Sheldrick, R. Christopher; Perrin, Ellen C.
The inadequacy of mental health and developmental services for children is a widely recognized and growing problem. Although a variety of solutions have been proposed, none has been generally successful or feasible. This research describes models of colocation that have evolved in primary care settings in Massachusetts and reports on pediatricians' and their colocated colleagues' impressions of their benefits and challenges. Pediatricians in 18 practices that included a colocated mental health/developmental specialist (MH/DS) were identified through a survey administered through the state American Academy of Pediatrics Chapter, and interviewed. Practices varied widely in the professional expertise/training and roles of the MH/DSs, communication among providers, and financial arrangements. The majority of pediatricians and MH/DSs reported being pleased with their colocated arrangements, despite the costs rarely being supported by billing revenues. This study suggests that further development of such systems hold promise to meet the growing need for accessible pediatric mental and developmental health care.